Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10067-017-3724-4
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against myelin sheath and S100β are associated with cognitive dysfunction in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) has been associated with cognitive impairment and peripheral production of autoantibodies. Autoantibodies against central nervous system (CNS) proteins and S100 calcium-binding β (S100β) were found increased in diseases characterized by cognitive impairment like Alzheimer disease and Neuropsychiatric Systemic Lupus Erythematosus (NPSLE). The aim of this study was to investigate the plasma levels of autoantibodies against myelin basic protein (anti-MBP), myelin oligodendrocyte glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Circulating autoantibodies may also contribute to poor cognition in RA. It has been shown that RA patients in remission had increased levels of autoantibodies targeting brain antigens, such as myelin basic protein and myelin oligodendrocyte glycoprotein, which inversely correlated with cognitive tests [88]. The same study reported increased plasma levels of central nervous system (CNS)-restricted proteins (S100β) in RA, indicating a dysfunctional blood brain barrier (BBB).…”
Section: Cognitive Impairment Depression and Anxietymentioning
confidence: 99%
“…Circulating autoantibodies may also contribute to poor cognition in RA. It has been shown that RA patients in remission had increased levels of autoantibodies targeting brain antigens, such as myelin basic protein and myelin oligodendrocyte glycoprotein, which inversely correlated with cognitive tests [88]. The same study reported increased plasma levels of central nervous system (CNS)-restricted proteins (S100β) in RA, indicating a dysfunctional blood brain barrier (BBB).…”
Section: Cognitive Impairment Depression and Anxietymentioning
confidence: 99%
“…During healthy aging, there is an increase in the levels of circulating autoantibodies, and this can be prematurely observed in RA. Of note, we have shown RA patients in remission had increased levels of autoantibodies specific for brain antigens, and this was inversely correlated with cognitive performance [44]. Therefore, the cognitive impairment in RA could also be explained by the detrimental action of CNS autoantibodies, as suggested by CNS demyelination observed in some RA patients [45].…”
Section: Rheumatoid Arthritismentioning
confidence: 83%
“…The participation of S100 group proteins in the formation of basic forms of congenital behavior and in the mechanisms of memory and learning has been proven experimentally (Hermann et al, 2012;Li et al, 2013;Baptista et al, 2017;Delgado-Moreno et al, 2017). Zhang et al (2009) reported a deterioration of cognitive characteristics in patients with depression and increased protein S100b, backed by Li et al (2014), who demonstrated that the S100b protein acts as a modulator of the inflamematory response of the hippocampus and plays a key role in reducing cognitive properties.…”
Section: Discussionmentioning
confidence: 98%